Climate change related risks, opportunities and adaptation actions in European cities - Insights from responses to the CDP cities program - Markus Groth; Maria Brück; Teresa Oberascher (European Regional Science Association (ERSA), 2016)
Cities, home to more than half of the world's population and important economic hubs, are vulnerable to impacts of climate change and worthy to protect. To address these challenges, implementing climate change adaptation measures is inevitable. The paper provides insights into climate change related risks, opportunities and adaptation actions based on responses by 40 European cities to the 2014 CDP Cities Information Request. The analysis shows that 92.5% of the responding European cities report that they face physical risks arising from climate change and that they identify more intense rainfall as the most relevant physical risk. Furthermore, more than half of the participants indicate that they are facing social risks due to climate change with increased risk to already vulnerable populations being the most important one. However, 72.5% of the cities report that they see economic opportunities arising from climate change. Already, 55% of the observed European cities indicate that they have implemented adaptation action plans and 82.5% of all cities are putting adaptation action into practice. The results point out that city governments show great awareness, interest and knowledge in addressing climate change issues, but however there is still demand for information and guidance. Moreover, the variety of answers shows that there is no 'one-size fits all solution' for cities to adapt to climate change. Thus, the findings can also serve as an innovative starting point for further research as well as the design and practical implementation of adaptation measures.
Keywords: H11; H41; Q54; Q58; R50; 330; adaptation actions; adaptation planning; CDP; cities; climate change; climate change adaptation; climate change opportunities; climate change risks